Tick-borne encephalitis - from pathogenesis to therapy - Palus, Martin (Jihočeská univerzita, 2016)
The proposed thesis contributes to the knowledge about tick-borne encephalitis and its pathogenesis. The thesis describes pathogenesis and immunopathogenesis of tick-borne encephalitis, impact of host's genotype in clinical course determination, immune response of patients with acute tick-borne encephalitis, the mechanism of tick-borne encephalitis virus migration into central nervous system and virus interaction with cells of neurovascular unit as well as potential medical interventions.
Tick-borne encephalitis - from pathogenesis to therapy
Tick-borne encephalitis - from pathogenesis to therapy
Keywords: tick-borne encephalitis; pathogenesis; immunopathogenesis; therapy; immune response; genotype; tick-borne encephalitis; pathogenesis; immunopathogenesis; therapy; immune response; genotype